Gamification in the Military - Sadiku, Matthew N. O.; Chukwu, Uwakwe C.; Sadiku, Janet O. (International Journal of Human Computing Studies, 2023)
In gamification, elements of game design are used to make an experience more engaging in a non-game context such business and the military. The role of gamification in military training is transforming the way our armed forces prepare for the modern battlefield. Gamification in the military training programs is becoming more engaging, effective, and efficient. The marriage of gamification and military training is a win-win situation. We can use gamification to boost training and take individual differences into account. This paper provides an overview on gamification in the military with examples.